Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1177/0021998312474046
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of monotonic mechanical properties for unidirectional glass fiber (U)/random glass fiber (R)/epoxy hybrid and non-hybrid polymeric composites

Abstract: The aim of this article is to study the variability in tensile, flexural, in-plane shear, and interlaminar shear properties of unidirectional glass fiber (U)/random glass fiber (R)/epoxy hybrid and non-hybrid composite laminates. Six kinds of laminated composites of average thickness 5.5 AE 0.2 mm and total fiber volume fraction (V fT ) ¼ 37% were manufactured using hand lay-up technique and tested under tensile, bending, in-plane shear, and interlaminar shear loading conditions. The failure modes of all test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 11 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…Many factors can affect test results, such as the fabrication method of the specimens, preparation, handling, storage, test rig design, and experimental technique. [ 55–57 ] The statistical scatter in the experimental test results, that is, coefficient of variation (C.V.), has been obtained as presented in Tables 5‐7. As shown in Table 5, the maximum C.V. for the ultimate tensile strength, Young's modulus, and strain to failure were observed to be 7.87% for F nanocomposite, 21.04% for G composite, and 13.57% for FHSHF nanocomposite, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Many factors can affect test results, such as the fabrication method of the specimens, preparation, handling, storage, test rig design, and experimental technique. [ 55–57 ] The statistical scatter in the experimental test results, that is, coefficient of variation (C.V.), has been obtained as presented in Tables 5‐7. As shown in Table 5, the maximum C.V. for the ultimate tensile strength, Young's modulus, and strain to failure were observed to be 7.87% for F nanocomposite, 21.04% for G composite, and 13.57% for FHSHF nanocomposite, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, through the injection of multiwalled carbon nanotube (MWCNT)-epoxy suspensions into stationary glass Eber mats, the interlaminar shear behavior was obviously enhanced. 2,[15][16][17][18] Selmy et al 20,21 studied the variability in the tensile, flexural, in-plane shear, and interlaminar shear properties of unidirectional glass fiber/random glass fiber/epoxy hybrid and non-hybrid composite laminates. They found that hybrid composites have higher ILSS than random composites, and the failure location of the hybrid laminates depends on not only the strength of the interface but also on the strength of the hybrid composite constituents.…”
Section: Introductionmentioning
confidence: 99%
“…These factors are specimen manufacturing, preparation, handling, storage, test rig design, and experimental technique. 85 Due to the above reasons, CV values of around 25% reflect the accuracy in the results. 86 Selmy et al 85 recorded maximum CV value of 16.8% for his static results.…”
Section: Resultsmentioning
confidence: 99%
“…85 Due to the above reasons, CV values of around 25% reflect the accuracy in the results. 86 Selmy et al 85 recorded maximum CV value of 16.8% for his static results. In another study, Selmy et al 72 recorded maximum CV value of 43.8% for his dynamic result.…”
Section: Resultsmentioning
confidence: 99%